Zwitterionic Conjugated Surfactant Functionalization of Graphene with pH‐Independent Dispersibility: An Efficient Electron Mediator for the Oxygen Evolution Reaction in Acidic Media. Issue 11 (19th February 2020) - Kim, Ungsoo; Cho, Yongjoon; Jeon, Dasom; Kim, Yongchul; Park, Sanghyeon; Seo, Jihyung; Lee, Junghyun; Oh, Nam Khen; Lee, Geunsik; Ryu, Jungki; Yang, Changduk; Park, Hyesung
Abstract: The functionalization of graphene has been extensively used as an effective route for modulating the surface property of graphene, and enhancing the dispersion stability of graphene in aqueous solutions via functionalization has been widely investigated to expand its use for various applications across a range of fields. Herein, an effective approach is described for enhancing the dispersibility of graphene in aqueous solutions at different pH levels via non‐covalent zwitterion functionalization. The results show that a surfactant with electron‐deficient carbon atoms in its backbone structure and large π–π interactive area enables strong interactions with graphene, and the zwitterionic side terminal groups of the molecule support the dispersibility of graphene in various pH conditions. Experimental and computational studies confirm that perylene diimide amino N ‐oxide (PDI–NO) allows efficient functionalization and pH‐independent dispersion of graphene enabled by hydration repulsion effects induced by PDI–NO. The PDI–NO functionalized graphene is successfully used in the oxygen evolution reaction as an electron mediator for boosting the electrocatalytic activity of a Ru‐based polyoxometalate catalyst in an acidic medium. The proposed strategy is expected to bring significant advances in producing highly dispersible graphene in aqueous medium with pH‐independent stability, thus broadening the application range of graphene. Abstract : pH‐independent dispersion stability of graphene in aqueous medium is achieved by non‐covalent zwitterion functionalization with perylene diimide amino N ‐oxide (PDI–NO) containing large π–π interactive area and electron‐deficient conjugated backbone, and a zwitterionic side terminal group. The as‐synthesized PDI–NO functionalized graphene is successfully applied to the oxygen evolution reaction as an electron mediator for enhancing the performance of homogeneous RuPOM catalyst.